Analysis of imaging differences between high-resolution CT and digital radiography chest films in pneumoconiosis screening - Lijuan LIU; Fenghong WANG (环境与职业医学)
Background The early lesions of pneumoconiosis that cannot be clearly shown by digital radiography (DR) chest films can be clearly displayed in high-resolution CT (HRCT). HRCT enables systematic observation of the evolution and progression of pneumoconiosis, providing reliable evidence for diagnosis.ObjectiveTo provide reliable evidences for the early screening of pneumoconiosis, By analyzing the imaging difference between HRCT and DR chestfilms in pneumoconiosis screening.MethodsSix casting workers in a casting forging company suspected of early stage of pneumoconiosis through regular occupational health examination screening were recruited , and 64 rows of spiral CT thin layer were scanned and reconstructed by high-resolution bone algorithm. Compare the imaging findings of early stage of pneumoconiosis small shadow on DR chest film and HRCT and make diagnostic conclusion. ResultsAll six subjects had Multiple small nodules and/or irregular shadows in the lungs were found in all six patients’ DR chest films, but the density and distribution of small shadows did not meet the diagnostic criteria of pneumoconiosis. The HRCT review showed that, dispersively distributed micro nodule shadows and/or short-thread shape thin shadows in the lung in four patients, the rest two patients' HRCT images showed multiple localized pleural thickening and partial calcification and multiple nodules like pleural uplift thickening. Other lesions were also identified, including lung multiple localized pleural thickening and calcification in 3 cases, lung multiple cystic bronchiectasis in 1 case, inflammatory nodules in 2 cases, of chronic lesions in 2 case. Through comprehensive analysis, early stage of pneumoconiosis were seen in 4 patients, among which 3 patients engaged in sand mixing and sand clearing presenting early stage of silicosis; 1 patient engaged in moulding sand manufacturing presenting early stage of foundry worker pneumoconiosis. ConclusionCompared with DR chest film, HRCT can more accurately show the morphology and distribution of lesions, and has significant advantages in identifying small shadows in early stage of pneumoconiosis and other lung diseases. The diffuse small nodules in the lung is not a characteristic manifestation of pneumoconiosis, and cannot be used as the basis for the diagnosis of early stage of pneumoconiosis alone. Even with a clear occupational dust exposure history, an early stage of pneumoconiosis diagnosis can be made after excluding other lung diseases. After dust work, especially silicon dust work workers showing abnormal changes in X-ray chest film, review of the HRCT should be conducted even if the small shadow distribution does not meet the diagnostic criteria of pneumoconiosis, so as to early detection of pneumoconiosis patients and high-risk groups.